Seroprevalence of flaviviruses antibodies in water buffaloes (Bubalus bubalis) in Brazilian Amazon - Casseb, Alexandre R (BioMed Central, 2014)
BACKGROUND: The state of Pará encompasses 26% of Brazilian Amazon where an enormous diversity of arboviruses has been found. This study aimed to assess the prevalence and distribution of hemagglutination-inhibition antibodies against antigens of six Flavivirus (yellow fever virus, Ilheus virus, Saint Louis encephalitis virus, Cacipacore virus, Bussuquara virus and Rocio virus) in water buffaloes in Pará state, Brazil. The prevalence of antibodies in these farm animals is important to determine the circulating arboviruses. FINDINGS: All investigated arboviruses were detected in the species studied and our results indicate that water buffaloes are susceptible to Flavivirus infection. Furthermore, there is solid evidence of active circulation of these viruses in the Brazilian Amazon. CONCLUSIONS: Water buffaloes showed higher prevalence of heterotypic antibody reactions and we hypothesized that they can serve as sentinels to detect the movement of such arboviruses in the Brazilian Amazon.